Usability Testing Analysis on The Bana Game as Education Game Design References on Junior High School (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Learning media is one of the important elements in the learning process. Technological development support makes learning media more varied. The approach of using digital technology as a learning media has a better and more effective impact than other approaches. In order to increase the students’ learning interest, it requires the support of an interesting learning media. The use of gaming applications as learning media can improve learning outcomes. The benefits of using the maximum application cannot be separated from the determination of application design. The Bana game aims to increase the ability of critical thinking of the junior high school students. The usability-testing analysis on the Bana game application is used in order to get the design reference as an educational game development. The game is used as an object of the analysis because it has the same characteristics and goals with the game application to be developed. Usability Testing is a method used to measure the ease of use of an application by users. The Usability Testing consists of learnability, efficiency, memorability, errors, and satisfaction. The results of the analysis obtained will be used as a reference for educational game applications that will be developed.